2002
DOI: 10.1002/cncr.10496
|View full text |Cite
|
Sign up to set email alerts
|

Randomized study of single early instillation of (2″R)‐4′‐O‐tetrahydropyranyl‐doxorubicin for a single superficial bladder carcinoma

Abstract: BACKGROUNDAlthough transurethral resection of a bladder tumor (TUR‐Bt) alone has been standard treatment for single superficial bladder carcinoma, some authors reported a certain prophylactic effect of a single immediate intravesical instillation of chemotherapeutic agent after TUR‐Bt. A prospective randomized study was conducted to determine whether a single (2″R)‐4′‐O‐tetrahydropyranyl‐doxorubicin (THP) instillation immediately after TUR‐Bt is beneficial to patients with a single superficial bladder carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 16 publications
4
41
0
Order By: Relevance
“…Water for injection irrigation achieved very similar RFR to those observed in the study of Okamura et al who included patients who received single intravesical chemotherapy (90% vs 92,4% in the first year, 83% vs 82,7% in the second year and 79% vs 78,8% in the third year) (Okamura et al, 2002). After a single postoperative intravesical instillation of mitomycin for low-risk tumors Solsona et al observed RFR of 98.2%, 84.2% and 80.7% in the first, second and third year respectively while our corresponding percentages were 90%, 83% and 79%, which indicates similar percentages in the second and third year of monitoring (Solsona et al, 1999).…”
Section: Discussionsupporting
confidence: 73%
“…Water for injection irrigation achieved very similar RFR to those observed in the study of Okamura et al who included patients who received single intravesical chemotherapy (90% vs 92,4% in the first year, 83% vs 82,7% in the second year and 79% vs 78,8% in the third year) (Okamura et al, 2002). After a single postoperative intravesical instillation of mitomycin for low-risk tumors Solsona et al observed RFR of 98.2%, 84.2% and 80.7% in the first, second and third year respectively while our corresponding percentages were 90%, 83% and 79%, which indicates similar percentages in the second and third year of monitoring (Solsona et al, 1999).…”
Section: Discussionsupporting
confidence: 73%
“…The present results corroborate those of Yamamoto et al (27), who reported that pirarubicin was not detected in the plasma after single intravesical administration of pirarubicin, and by a report by Okamura et al (17), who reported that there were no severe local toxicities after a single dose of pirarubicin for 60 min.…”
Section: Discussionsupporting
confidence: 93%
“…The concentration of pirarubicin in the tumor tissue becomes markedly high in a relatively short time after administration into the bladder (15). It is reported that the intravesical instillation with pirarubicin produces an antitumor effect against bladder cancer, and that the prophylactic effect of recurrence in the bladder after intravesical instillation chemotherapy with pirarubicin is higher than that after TUR-BT only (17). Moreover, short-time intravesical instillation chemotherapy is performed to obtain a greater antitumor effect and to prevent an increase in side effects, as this method has the advantage of a higher penetration of pirarubicin into bladder tumor tissues (18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 91 patients in our cohort with NMIBC. The recurrence rate of these patients (17.6%, 16/91) was similar to the results reported by Okamura et al [15]. The results of our research showed that rs1056892 on CBR3 and rs1799983 on NOS3 were significantly associated with tumor recurrence risk after TUR and intravesical instillations of THP in patients with NMIBC.…”
Section: Discussionsupporting
confidence: 80%